The impact of percutaneous coronary intervention versus coronary artery bypass grafting surgery in left main coronary disease. (26th April 2021) - Oliveira, CC; Guerra, A; Braga, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Although coronary artery bypass grafting (CABG) has been considered the gold-standard method for the treatment for left main stable ischemic coronary disease (s-LMCAD), percutaneous coronary intervention (PCI) has shown good results. Objective: To evaluate patients with s-LMCAD who performed CABG or PCI and compare their outcomes. Study design: Single center, retrospective study that included all s-LMCAD patients who performed LM PCI or CABG between January 2015 and November 2018 (n = 35 in the PCI group and 35 in the CABG group after propensity score and matches in a ratio of 1:1). Clinical and imaging information of patients was collected, relating to the pre- and post-procedure and with 3 years of follow-up (FUP). Results: Overall, baseline clinical and angiographic characteristics were balanced between the groups. The PCI group had higher prevalence of previous coronary disease (54.3%% vs 28.6%, p = 0.029) and chronic obstructive pulmonary disease (22.9% vs 5.7%, p = 0.04). The anatomical complexity estimated through the calculation of the SYNTAX score showed no significant differences between groups (16 vs 19, p = 0.151). 50% of PCI group performed IVUS, 2.8% OCT and 2.8% FFR. All CABG grafts used were arterial. There were no registries of events during hospitalization. At 30 days, cardiovascular-mortality was higher in the PCI group than in CABG group (n = 2 (5.56%) vs 0, respectively), representing all cases of cardiovascular death in PCI group through the 3-years follow-up. In CABG group, cardiovascular-related death was more substantial at 3 years. At 3 years of FUP, no significant differences were found between the PCI and CABG groups in MACCE (hazard ratio (HR) of the PCI group, 2, 786; confidence interval (CI) of 95%, 0.873 to 8, 889; p = 0.084). However, patients submitted to PCI with a SYNTAX score≥23 had worse MACCE results (HR 9.022, 95% CI, 1, 054 to 77.210; p = 0, 045), though a large confidence interval was also registered. Though not significantly different, cardiac-related hospital admissions were more frequent in the CABG group (18 (25.00%) vs 6 (16.67%) in the PCI group), but occurred more acutely in the PCI group (< 30 days). Stroke events happened more frequently in the CABG group, with a total of 4 cases reported (5.56%) whereas in the PCI group none happened. Myocardial infarction rate was also higher in the PCI group (2, 5.71%) and 1 happened in the first 30 days which was related to a target lesion failure. Revascularization through PCI due to restenosis had only 1 (2.78%) case registered. Graft failure happened in only 1 patient. Conclusion: In conclusion, for the treatment of patients with stable s-LMCAD and low anatomical complexity, PCI was noninferior to CABG. Our results suggest that PCI is an acceptable alternative to CABG for patients with stable left main coronary artery disease, except for the ones with high anatomical complexity.